PENGARUH PROMOSI TERHADAP PREFERENSI PRODUK PEMBIAYAAN MURABAHAH - Umi Faizah; Muhammad Nur Ihwan Afif; Maslihan M. Ali (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2018)
This research entitled Effect of Promotion on Murabahah Financing Product Preferences (Case Study in KSPPS BMT Bina Ummat Sejahtera Branch Pati). This study aims to find out: (First) knowing the promotion strategy of murabahah financing by account officer (AO) to prospective members in KSPPS BMT Bina Ummat Sejahtera Branch Pati Branch Pati, and (Second) Knowing the influence of promotions made by account officers (AO) in KSPPS BMT Bina Ummat Sejahtera Branch of Branch Pati against murabahah financing product preferences. The type of research used is field research using a quantitative approach. The population in this study were Murabahah financing customers in KSPPS BMT Bina Ummat Sejahtera Branch Pati as many as 60 people. The sampling technique uses Probability Sampling. The sampling technique is Simple Random Sampling technique. Data collection methods for questionnaires that have been tested for validity and reliability. Data analysis techniques include linear regression analysis, partial t test, and simultaneous f test. The results of this study indicate that: (First) promotion strategy of murabahah financing by account officer (AO) to prospective members in KSPPS BMT Bina Ummat Sejahtera Branch Pati by offering directly to the community, using both print and social media and providing murabahah financing services to the public. (Second) promotion conducted by account officer (AO) at KSPPS BMT Bina Umm Sejahtera Branch Pati gives influence to murabahah financing product preferences to choose murabahah financing in KSPPS BMT Bina Ummat Sejahtera Branch Pati, this can be seen from the significance value of promotion influence on financing preferences murabahah of 0.000 <0.05, then the hypothesis is acceptable.